2021
DOI: 10.1088/1755-1315/753/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Decarbonizing the electricity system in Sumatra region using nuclear and renewable energy based power generation

Abstract: The Indonesian national energy policy mandates that the new and renewable energy in 2025 reaches a share of 23% and in 2050 rises a share of 31% in the primary energy mix. The energy mix by types is further detailed in the national energy plan (RUEN). Since Indonesia is committed to participating in efforts to mitigate global climate change, the energy sector is expected to contribute to the greenhouse gas (GHG) reduction target of up to 29% (unconditional) and 41% (conditional) under Business as Usual (BAU) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The study confirmed that fossil fuel is a major source of greenhouse gas emissions and a driver of carbon intensity [58,78]. Most authors concluded that promoting clean and alternative energy sources as an alternative to fossil fuels reduces carbon emissions [80,85,89].…”
Section: Impact Of Greenhouse Gas Emissions On Climatementioning
confidence: 61%
See 1 more Smart Citation
“…The study confirmed that fossil fuel is a major source of greenhouse gas emissions and a driver of carbon intensity [58,78]. Most authors concluded that promoting clean and alternative energy sources as an alternative to fossil fuels reduces carbon emissions [80,85,89].…”
Section: Impact Of Greenhouse Gas Emissions On Climatementioning
confidence: 61%
“…Based on a panel cointegration analysis of 12 major nuclear generating nations to determine the impact of nuclear power, energy supply, and income on CO 2 emissions, it was concluded that nuclear energy reduces CO 2 emissions [124]. Other researchers have asserted that including nuclear power in the energy mix is essential for achieving GHG emissions and carbon intensity targets while ensuring adequate energy security [78,81,85]. According to a study on Egypt's energy mix, nuclear power plants (NPPs) have low external damage costs and minimal environmental impact during normal operation.…”
Section: Nexus Between Nuclear Energy Generation and Thementioning
confidence: 99%